The character of the Syriac version of Psalms : a study of Psalms 90-150 in the Peshitta - Carbajosa, Ignacio, 1967- (Monographs of the Peshiṭta Institute, Leiden. Studies in the Syriac versions of the Bible and their cultural contexts,, 2008)
This book investigates the character of the Peshitta in Psalms 90-150 in order to facilitate the proper use of this version in textual criticism. It identifies the Peshitta's translation techniques and it discusses the version's interpretation of difficult passages in the Hebrew text. The question of the Hebrew Vorlage behind the Peshitta Psalter is raised. Also investigated here is the relationship between the Peshitta Psalms and the LXX and Targum, and an assessment of the supposed influence of these versions on the Peshitta Psalter is offered. Inquiry is made into the theology of the translation, the identity of the translators, and the relationships among the manuscripts of the Peshitta Psalter. This text is designed as a tool for scholars who, when confronted by critical questions in the Psalter, seek to understand the readings preserved in the Peshitta.